EFEKTIVITAS PENGGUNAAN MEDIA GAMBAR DALAM PEMBELAJARAN BAHASA ARAB - Hilmi Hilmi (UIN AR-RANIRY, 2016)
Learning is as an effort to change behavior in a person either changes in the level of knowledge, skills, or attitudes that deliver ones to the happiness in the world and the hereafter. In education, there are several factors that can support the implementation of the learning process, the most important factor is the availability of adequate learning media and enjoyable. Media images or photographs are pleasant enough media in Arabic learning, especially in learning Mufradat (vocabulary). By using the media, the purpose of the learning will be achieved as expected. This writing attempts to reveal the effectiveness of the media images or photographs in Arabic learning.